Probucol and ciprofibrate effects on lipid peroxidation, blood rheology, and angina pectoris clinical course - A. N. Zakirova; A. V. Perevalov; N. E. Zakirova (Кардиоваскулярная терапия и профилактика)
Aim. To investigate hypolipidemic and antioxidant effects of probucol and ciprofibrate, their influence of blood rheology and clinical course of angina pectoris, during monotherapy and combined therapy, as a part of coronary heart disease (CHD) complex management. Material and methods. The study included 112 CHD patients, who were administered probucol (n=39), ciprofibrate (n=37), or their combination (n=36) for 3 months. Before the treatment, all participants were administered placebo for one month. The authors used clinical, instrumental (angina episodes frequency assessment, veloergometry), and biochemical methods (measuring levels of lipid fractions, lipid peroxidation (LP) products, antioxidant enzymes, fibrinogen and antithrombin III, as well as red blood cell and platelet aggregation). Results. Combined with standard antianginal therapy in CHD patients, probucol substantially decreased LP product levels, activated glutathione peroxidase and superoxide dismutase, inhibited red blood cell and platelet aggregation. Ciprofibrate improved lipid profile, decreased fibrinogen level, and increased antithrombin III level. Combined therapy by probucol and ciprofibrate demonstrated greater hypolipidemic, antioxidant, hemorheological, and clinical effects than monotherapy. Conclusion. Probucol and ciprofibrate can be used as monotherapy and in combination for CHD complex management, asmedications that have not only hipolipidemic action , but also antioxidant, hemorheological and antianginal effects.